Software engineering's role in visualizing large data as medical datasets - Abdel Amir Sebti, Hind; A. Najim, Safa (Journal of Advanced Computer Science & Technology, 2022)
Although both 'information visualization' and ‘software engineering visualization' are data collection operations, their motivations are clearly distinct. The visualization of software engineering integrates the original design modules and identifies the connections between the main components. The purpose of software engineering is to develop high-quality programs and create appropriate work. The goal of visualization is to get insight into many components of a process we are interested in, such as a scientific simulation or a real-world process, using interactive graphs. Medical imaging techniques are used to detect and comprehend illness progression in the human body. To be able to make a diagnosis concerning it. In health centers and hospitals, managing vast collections of medical pictures is a challenge. Because the image database has grown in size over the last year, meaningful information is needed to assist the specialist in assessing the patient's condition. In this review, we will highlight some of the techniques that we use in data analysis.